Randomised clinical trial: mesalazine (Salofalk granules) for uncomplicated diverticular disease of the colon – a placebo‐controlled study. Issue 7 (17th February 2013) - Kruis, W.; Meier, E.; Schumacher, M.; Mickisch, O.; Greinwald, R.; Mueller, R.; ,
Summary Background Robust evidence regarding medical intervention for symptomatic uncomplicated colonic diverticular disease (DD) is sparse. Aim To investigate mesalazine (Salofalk granules) in this setting. Methods In a double‐blind, placebo‐controlled, multicentre, 6‐week trial, patients were randomised to mesalazine 1000 mg three times daily or placebo. Primary efficacy endpoint was change in lower abdominal pain to week 4 (baseline defined using pain score from 7 days pre‐treatment). Results Median change in lower abdominal pain with mesalazine vs. placebo was −37 (n = 56) vs. −33 (n = 61) [P = 0.374; 95% CI (−11; 4)] in the intent‐to‐treat (ITT) population, and −41 (n = 40) vs. −33 (n = 51) [P = 0.053; 95% CI (−18; 0)] in the per‐protocol (PP) population, i.e. the primary endpoint was not significantly different. Post hoc adjustment for confounding factors ('baseline pain intensity', 'baseline symptom score (Brodribb)', and 'localisation of diverticula in the descending colon') resulted in P = 0.111 [ITT, 95% CI (−15.4; 1.6)] and P = 0.005 [PP, 95% CI (−19.7; −3.5)]. Between‐group differences increased using pain score on day 1 as baseline, and reached significance for the PP population [mesalazine −42, placebo −26, P = 0.010; 95% CI (−25; −3)]. Median change in combined symptom score from baseline to week 4 was 257 mm with mesalazine vs. 198 mm with placebo [P = 0.064; 95% CI (−3; 105)]. More placebo‐treated patients received analgesic/spasmolytic concomitant medication (34.4% vs. mesalazine 21.4%), indicating improved pain relief with mesalazine (P = 0.119). Safety was comparable. Conclusions A daily dose of 3.0 g mesalazine may relieve pain during a symptomatic flare of uncomplicated DD. In this, the first placebo‐controlled double‐blind trial in acute uncomplicated DD, mesalazine showed promising therapeutic efficacy.